(untitled) (Italian Journal of Public Health, 2010)
Canada faces health care challenges common to all industrialized countries – how to ensure timely access to high quality care, close to home, at an affordable cost. Addressing these challenges is complicated by inter- jurisdictional variation in both how health care is managed and delivered, and in health outcomes. Canada can be described as a non-system of 10 provincial and three territorial health insurance plans which mandate publicly-funded coverage for medically necessary hospital and physician services, based upon common principles and shaped by a federal governance structure that affords substantial power and autonomy to the provinces/territories over matters of health and health care. This article first examines the structural context of the health care system in Canada, including the range of services publicly funded, the public-private mix, and the complexities of current governance arrangements. It then discusses several issues affecting health policy reform: costs versus access; questions of sustainability, quality, and performance; human resources capacity; and the provision of public and population health services.